The Turkish diaspora landscape in Western Europe: Between the AKP's power aspirations and migrants' grievances - Sinem Adar; Yaşar Aydın; Cengiz Günay; Günter Seufert (Stiftung Wissenschaft und Politik (SWP), 2024)
The AKP leadership's diaspora policy has created tensions between Turkey and European countries. Turkey's gradual slide into authoritarianism, Islam's steady expansion into public life and the increasing divergence between the foreign and security policies of Turkey and the EU have deepened the mistrust in relations between that country and the Union. Concerns abound about Ankara's "long-arm" influence and the loyalties of Turkish migrants and their foreign-born children to their countries of residence. Meanwhile, the mainstreaming of anti-migration and anti-Islam sentiments in European countries has led to a conflation between Ankara's ambitions and the diaspora's attitudes and demands in the public discourse. While it is crucial not to overstate the AKP's ability to mobilise the diaspora, the genuine grievances of individuals with a migration background should be taken seriously. At the same time, European governments should continue to advocate the greater independence of mosque communities from Turkey's influence in order to maintain a balanced diaspora landscape.
Keywords: 320; Diaspora policy; Justice and Development Party; AKP; Turkish migrants; Kılıçdaroğlu; Diyanet; DITIB; assimilation; new subjectivity; islamophobia; Gülenist network